Minimally Invasive (Percutaneous) Pedicle Srews as the Treatment of Choice in Thoracolumbar Spine Fractures - Zygmunt Siedlecki; Maciej Śniegocki (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Minimally invasive techniques of transpedicular fusion have become very common and seem to displace classical open techniques. Pedicle screws fusion is the procedure of choice in unstable traumatic lumbar and thoracic spine fractures of. Aim. The aim of the study was to answer whether open techniques are still used in injuries or whether they have been completely replaced by MISS. Material and Methods. The manuscript presents an analysis of patients treated in 2017–2021 in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery of Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University. Results. Based on the analysis of medical documentation, it was found that every case of traumatic thoracolumbar spine fracture in 2017–2021 was treated using minimally invasive techniques. According to the documentation, the last case of using open surgical technique in the case of trauma was in 2016. It was noted that percutaneous techniques dominated the surgical treatment of thoracolumbar spine fractures and replaced the classic techniques in our department, which are used only, in some cases, in treatment of non-traumatic spondylolisthesis. Conclusions. Therefore, percutaneous techniques are currently the procedure of choice in spine injuries fusion in our hospital. The use of percutaneous techniques reduces the surgical traumatization of tissues (it is important to avoid additional traumatization and blood loss in traumatic patients). It has been pointed out that these procedures are performed by neurosurgeons who, in teaching process, used percutaneous techniques often and now prefer this method. The use of percutaneous techniques has important aspect in the field of neurosurgical nursing, because care of the operated area consists in observing few (4–16) smaller wounds, not one long wound (as in classic techniques), and these wounds are located directly above the titanium screw tips, which must under neurosurgical nurse care. (JNNN 2022;11(1):3–7)